2016
DOI: 10.14814/phy2.12981
|View full text |Cite
|
Sign up to set email alerts
|

Typical gray matter axons in mammalian brain fail to conduct action potentials faithfully at fever-like temperatures

Abstract: We studied the ability of typical unmyelinated cortical axons to conduct action potentials at fever‐like temperatures because fever often gives CNS symptoms. We investigated such axons in cerebellar and hippocampal slices from 10 to 25 days old rats at temperatures between 30 and 43°C. By recording with two electrodes along axonal pathways, we confirmed that the axons were able to initiate action potentials, but at temperatures >39°C, the propagation of the action potentials to a more distal recording site was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Since one axon serves all synapses in an autaptic neuron, the disruption of action potential propagation before reaching the first synapses results in the complete loss of eEPSCs. Interestingly, it was reported that warming cortical slices (42 °C), which makes membranes more liquid, similarly to cholesterol depletion, also results in action potential propagation failure 47 . The search for the mechanism of the disruption of action potential propagation in cholesterol-depleted axons exceeds the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Since one axon serves all synapses in an autaptic neuron, the disruption of action potential propagation before reaching the first synapses results in the complete loss of eEPSCs. Interestingly, it was reported that warming cortical slices (42 °C), which makes membranes more liquid, similarly to cholesterol depletion, also results in action potential propagation failure 47 . The search for the mechanism of the disruption of action potential propagation in cholesterol-depleted axons exceeds the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using squid giant axons demonstrated that changes in steady state bath temperature profoundly altered the AP duration and amplitude [33]. A recent study using unmyelinated axons in the rat cerebellum and hippocampus showed that raising bath temperature reduced or blocked CAPs [39]. In general, the AP amplitude and duration decreased when the bath temperature was raised.…”
Section: Mechanisms Underlying Infrared Induced Inhibition and Actionmentioning
confidence: 95%
“…In such experiments, a failure at the first stimulus increased the failure rate at the second stimulus (changed from 50% to 75% failures at 30 ms interval), suggesting a slightly reduced excitability after a single stimulus. In contrast, a success on the first stimulus almost eliminated failures at the second stimulus (<0.1% failures, Pekala et al, 2016). This means that the excitability-increasing effect of a spike in the tested unit's axon was much stronger than the influence from adjacent synchronously activated axons.…”
Section: Tca Post-spike Hyperexcitability—an Axonal Membrane Mechanismentioning
confidence: 98%
“…To summarize, increases in population propagation speed and amplitude are robustly demonstrated in whole animals (Gardner-Medwin, 1972), cerebellar and hippocampal slices (Wigström and Gustafsson, 1981), at temperatures between 22 and 35°C (Soleng et al, 2004; Pekala et al, 2016), and in peripheral cold-sensitive C-fibers and sympathetic axon in humans (Bostock et al, 2003).…”
Section: Tca Post-spike Hyperexcitability—an Axonal Membrane Mechanismentioning
confidence: 99%
See 1 more Smart Citation